Biofuels from agricultural wastes and byproducts - Blaschek, Hans P.; Ezeji, Thaddeus C.; Scheffran, Jurgen (Wiley-Blackwell, 2010)
Traditional agriculture and emerging biofuels technology produce a number of wastes and by-products, ranging from corn fiber and glycerin to animal manure, that have the potential to serve as the basis for additional sources of bioenergy that includes both liquid biofuels and biogas